EFEK PENAMBAHAN GASKET KEPALA SILINDER DAN VARIASI OKTAN BENSIN TERHADAP PERFORMA MESIN SILINDER TUNGGAL - Rahmat, Bahtiar; Wijaya, Mohammad Burhan Rubai; Bahtiar, Fahmy Zuhda; Muttaqin, Katiko Imamul; Wirawan, Yuris Bahadur (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
The total motor vehicle sales reflected an increase in people's mobility. Alongside this, the industry were also develop high compression engines to achieve optimal performance. This research aims to examine the effects of adding a cylinder head gasket and variations in the octane number of gasoline used in a single-cylinder internal combustion engine. Dynamometer testing was conducted to observe the differences in torque and power output. The test results indicate that an engine with a compression ratio of 11,8 Kg/cm2, coupled with the use of RON 100 gasoline, produces the highest power output, which is 7.90 kW, with peak torque reaching 9.93 Nm. On the other hand, the smallest torque is generated by the same engine when supplied with RON 92 gasoline, at 4.78 Nm, with the lowest power output of 5.43 kW.